IMPLEMETASI KURIKULUM MERDEKA DI SEKOLAH DASAR (STUDI MULTIPERSPEKTIF) - Nisaul Khaira (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2023)
This study aims to analyze the implementation of the merdeka curriculum in elementary schools from various perspectives, specifically regarding understanding, execution, challenges, and the efforts undertaken during the implementation process. The study employs a qualitative approach using a multi-perspective case study method. data were collected through interviews, observations, and documentation involving teachers, school principals, and other stakeholders involved in the curriculum's implementation. The data were analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results indicate that the implementation of merdeka curriculum provides teachers with greater flexibility to develop instruction tailored to the needs and characteristics of their students. however, implementation still faces several challenges, including uneven levels of teacher understanding, limited learning resources and supporting facilities, difficulties in preparing instructional materials, and challenges in applying assessments that align with the curriculum's principles. from various perspectives, successful implementation is heavily influenced by teacher competence, principal leadership, school support, the availability of facilities and infrastructure, and continuous professional development. consequently, strengthening teacher competence, providing ongoing guidance, and ensuring institutional support are essential for the optimal implementation of merdeka curriculum in elementary schools.